1999
DOI: 10.1016/s0008-6363(99)00148-0
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase colocalizes with signs of lipid oxidation/peroxidation in human atherosclerotic plaques

Abstract: Ceroid, nitrotyrosine and NOS II colocalized in late stages of atherosclerosis and were found around the necrotic core in the plaque. This could suggest that NOS II expression in macrophages is involved in oxidation and peroxidation of lipids, leading to ceroid formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 32 publications
4
66
0
2
Order By: Relevance
“…This is paralleled with the decreased mRNA and protein expression for eNOS and iNOS, suggesting that LDL treatment resulted in a transcriptional down-regulation of NOS mRNA and protein expression that led to the decreased NO-mediated endothelium-dependent vasodilation. As an important endothelium-derived signal mediator, NO plays key roles in vasodilation (Schulz et al, 2008) and cardiovascular disease pathogenesis (Cromheeke et al, 1999). A report showed that atherosclerotic lesions containing foam cells were induced in a model of atherosclerosis in rabbits with moderate hypercholesterolaemia by chronic inhibition of NOS (Kitahara et al, 2010), revealing the importance of NO system in the progression of atherosclerotic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This is paralleled with the decreased mRNA and protein expression for eNOS and iNOS, suggesting that LDL treatment resulted in a transcriptional down-regulation of NOS mRNA and protein expression that led to the decreased NO-mediated endothelium-dependent vasodilation. As an important endothelium-derived signal mediator, NO plays key roles in vasodilation (Schulz et al, 2008) and cardiovascular disease pathogenesis (Cromheeke et al, 1999). A report showed that atherosclerotic lesions containing foam cells were induced in a model of atherosclerosis in rabbits with moderate hypercholesterolaemia by chronic inhibition of NOS (Kitahara et al, 2010), revealing the importance of NO system in the progression of atherosclerotic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The intensities of bands were analyzed by Quality One Image software (BioRad). The eNOS and iNOS mRNA levels were normalized to the ␀-actin mRNA signal (40). Western blotting and NO synthase activity.…”
Section: Methodsmentioning
confidence: 99%
“…During the process of atherosclerosis development, the endothelial function is impaired. Therefore, the endothelium-derived cNOS expression or activity as well as the production of endothelial NO is decreased, whereas the activity of vascular smooth muscle cell (VSMC)-expressed iNOS is increased,11,12 resulting in increased NO free-radical production, which stimulates cell apoptosis and collagen degradation and promotes the development of atherosclerosis 11,13. NO free radicals could also synthesise peroxynitrite through a reaction with superoxide anion, thus causing further tissue damage 12…”
Section: Discussionmentioning
confidence: 99%